Territórios em resistência: educação ambiental crítica em escolas do campo: uma análise a partir do curso de extensão escolas sustentáveis e Com-Vida/UFSM - Kist, Anna Christine Ferreira (2019)
This thesis refers to the educational territories of Critical Environmental Education and Rural Education and their articulation through a praxis, a critical, emancipatory and transformative education. In this sense, this work aimed to understand how Critical Environmental Education, dialogues with Campo Education in Campo schools that participated in the extension project Environmental Education - Sustainable Schools and With Life / UFSM. As specific objectives: 1.Problematize the concepts of critical environmental education, campo education and campo school. 2. To analyze the action Secad/Secadi's performance in the areas of environmental education and campo education in the Lula and Dilma Governments and the repercussions of their extinction in the current government. 3. Verify if the extension project of Environmental Education Sustainable Schools and With Life/UFSM promoted changes in the teaching practices of the researched schools. 4. Identify and discuss the design that guides teaching practices in these schools. 5. Find out if Critical Environmental Education and Campo Education are present in these schools and how they are articulated through a pedagogical praxis. 6. Propose ways for the strengthening of Critical Environmental Education and Campo Education in the continuous and permanent formation of teachers. In this investigation we used the dialectical method, qualitative methodology with conceptual theoretical approach in the dialectical method, investigative case study modality. Finally, it is concluded that Critical Environmental Education and Campo Education, dialogue and articulate from the theoretical foundations of Critical Theory, based on Marxist authors, the great Educator Paulo Freire, Popular Education and the pedagogical praxis present in schools searched.